25-Hydroxy-vitamin D level may predict presence of coronary collaterals in patients with chronic coronary total occlusion - Dogan, Yasemin; Sarli, Bahadir; Baktir, Ahmet Oguz; Kurtul, Serkan; Akpek, Mahmut; Sahin, Omer; Odabas, Huseyin; Dondurmacı, Engin; Ugurlu, Mehmet; Ozkan, Eyup (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Sufficient coronary collateral circulation (CCC) protects myocardial tissue against ischemia in patients with coronary chronic total occlusion (CTO). Vitamin D is a steroid hormone which has been related to increased prevalence of hypertension, left ventricular hypertrophy, heart failure, peripheral artery disease, coronary artery disease, myocardial infarction and cardiovascular mortality. Aim : To investigate whether there is an association between serum 25-hydroxy-vitamin D levels and development of CCC in patients with coronary CTO. Material and methods : A total of 188 patients with CTO at coronary angiography were included in this study. Vitamin D and parathyroid hormone (PTH) levels were measured on the day of coronary angiography. Development of collateral circulation was graded according to the Rentrop classification after coronary angiography. Then, patients were divided into two groups on the basis of CCC grades: group 1 included 68 (36%) patients with poorly developed CCC, and group 2 included 120 (64%) patients with well-developed CCC. Results : Patients with poorly developed CCC had significantly lower serum 25-hydroxy-vitamin D levels compared to those with well-developed CCC (20 ±3 vs. 30 ±6 ng/ml, p < 0.0001). Multivariate logistic regression analysis indicated serum 25-hydroxyvitamin D (25(OH)D) (OR = 1.794, 95% confidence interval (CI): 1.453–2.216; p < 0.001) as an independent predictor of poor collateral flow in patients with CTO. Conclusions : Low vitamin D level is an independent predictor of poor CCC in patients with CTO.